(untitled) (The Pakistan Development Review, 2000)
Recent estimates show that after falling in the 1980s, poverty has made a comeback in Pakistan during the 1990s. The Government of Pakistan (GOP) estimate show an increase in caloric poverty headcount from 17 percent in 1987-88 to 33 percent in 1998-99 and also rising income inequality during the 1990s.1 In contrast preliminary estimates by the World Bank show that poverty may not have risen as rapidly during the 1990s and may even have stagnated.2 Slow down in economic growth, rising open unemployment, rising food and non-food prices, reduction in the fiscal space for pro-poor public programmes, poor governance hampering delivery of social services to the poor; are factors that have been attributed to the growing poverty and vulnerability of households in recent years.